Evaluation of land suitability on arabica coffee plantation by parametric method in Lintongnihuta District. (May 2019) - Marbun, P; Nasution, Z; Hanum, H; Karim, A
Abstract: This study aims to establish the land suitability class and improvement efforts that need to be done in each of the Soil Map Unit (SMU) on arabica coffee fields in Lintongnihuta district. Results of overlaying the map of soil type, the map of altitude and slope map with a scale of 1: 50, 000 produced 13 SMU. Evaluation of several soil characteristics (texture, coarse fragment, CaCO3 and salinity) must consider the appropriate soil depth, where the normal root depth of the Arabica coffee plant is 150 cm, so that it uses 6 (six) parts of the depth of the soil with a depth of 25 cm for each section. Correction indexes used in succession are: 2.00 - 1.5 - 1.00 - 0.75 - 0.5 - 0.25.The results showed that all SMU in Arabica coffee land in Lintongnihuta District has the actual land suitability class S3 (f) (marginally suitable, limiting factor: soil fertility). Improvement efforts that can be done are: giving lime, organic material, fertilization and reclamation. All SMU has the potential land suitability classS2 (c, s)(moderately suitable, limiting factor: climate and natural soil).